Spinal Brucellosis Masquerading as Pyogenic Spondylodiscitis: A Rare Case - Salim, Azizul Akram; Nik Hassan, Nadiah; Haron, Juhara; Johari, Joehaimey; Yusof, Mohd Imran (IIUM Medical Journal Malaysia, 2022)
Brucellosis is a zoonotic infection secondary to Brucella spp. Musculoskeletal system is the most affinity site to been affected by this disease and lumbar vertebrae the most favourite site of involvement. The disease can manifest as focal or diffuse. The dietary history is a main and good clinical clue towards the definite diagnosis. Plain radiograph may benefit in terms of focal disease, however MRI is the most sensitive and appropriate imaging to look for extension of the disease and spinal complications. We are reporting a case of spinal Brucellosis in a lady who was initially diagnosed as pyogenic and tuberculous spondylodiscitis. Patient’s initial presentation as well as the radiological investigation led towards the diagnosis of pyogenic spondylodiscitis, however the blood culture revealed Brucella melitensis. We would like to highlight the importance of clinical history and challenges in diagnosing spinal Brucellosis as radiographic manifestation is non-specific and the organism are almost forgotten nowadays.